The Best Grammar Workbook Ever! : Grammar, Punctuation, and Word Usage for Ages 10 Through 110 - Miller, Arlene, ....- (California : bigwords101, 2015)
The Best Grammar Workbook Ever includes everything you need to become a better writer and speaker. From words, phrases, clauses, and sentences to punctuation, capitalization, and common writing problems - this book contains it all, with easy-to-understand examples and over 100 exercices and chapter tests. Lists of commonly misspelled and mispronounced words, common word roots, writing tips, a glossary, answer key, and index are included.
Keywords: Engelse spraakkunst